DOES WATER, HYGIENE, AND SANITATION INDEED DIRECTLY AFFECT CHILDREN’S STUNTING? : A SCOPING REVIEW - Martias, indra (International Journal of Social Science, 2024)
Water, sanitation, and hygiene (WASH) refers to the widespread problem of insufficient access to clean water, appropriate sanitation, and effective hygiene practices. Inadequate WASH practices can lead to health issues, including diarrheal illnesses, which hinder children's development and make it more difficult for them to absorb vital nutrients. This study aimed to identify and extract the essential features and components of stunting determinants, including water, sanitation, and hygiene. This research was categorized as a scoping review because it did not appraise or analyze the methodological quality of the included studies. A scoping review design was employed in this investigation. The PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) criteria were used in this study. A thorough search was carried out using ScienceDirect, EBSCO, and PubMed to find papers published between 2014 and 2024. According to research results, it is currently believed that there are determinant factors that influence stunting, such as water, cleanliness, and sanitation. This has a significant impact on the children’s development. Stunting in children under five years of age is at risk due to unclean environments and poor sanitation. Enhanced sanitary facilities and on-site water availability improved the health of expectant mothers and children. Studies have indicated that WASH treatment significantly improves children under five years old with a mean height-for-age z-score